Validation Analysis of LMS-BIDAK for Literacy Learning in Higher Education - Kurniaman, Otang; Hadriana, Hadriana; Islami, Nur; Putra, Zetra Hainul; Radini, Radini (Institut Teknologi Pendidikan Indonesia, 2026)
The development of technology has changed literacy learning so that it is necessary to develop a Learning Management System (LMS)-BIDAK (Bacalah (Read), Identifikasi (Identify), Diskusikan (Discuss), Aksi (Action), Kesimpulan (Conclusion)) before it is used, the product that has been developed needs to be validated. The purpose of the study was to see the validation of the LMS-BIDAK product so that it is suitable for use in literacy learning. The research method used was a quantitative method with nine expert validators in language, media and content. The results of the study were taken from the assessment of media experts with an average of LMS-BIDAK design of 93.75 with a very good category, LMS-BIDAK software of 92.26, and LMS-BIDAK benefits of 95.83 very good. The assessment of language experts on the aspect of content feasibility with an average of 93.75 very good, the aspect of presentation feasibility of 89.58 good, the linguistic aspect of 88.1 good, and the graphic aspect of 93.1 very good. The assessment of material/content experts on the learning design aspect was 88.89 good, the material aspect with an average of 91.67 was very good, and the benefit aspect in the content was 95.84 very good, so it is concluded that LMS-BIDAK is suitable for use in literacy learning in higher education.